The Effect of Open-Air Waste Burning on Infant Health: Evidence from Government Failure in Lebanon - Pierre Mouganie; Ruba Ajeeb; Mark Hoekstra (Institute of Labor Economics (IZA), 2020)
An estimated 40 percent of the world's garbage is burned in open-air fires, which are responsible for as much as half of the global emissions of some pollutants. However, there is little evidence on the health consequences of open-air waste burning. In this paper, we estimate the effect of in utero exposure to open-air waste burning on birth outcomes. We do so by examining the consequences of the Lebanese garbage crisis of 2015, which led to an abrupt, unanticipated increase in waste burning in residential neighborhoods in Beirut and Mount Lebanon. To identify effects, we exploit variation in exposure across neighborhoods before and after the crisis. Results indicate exposure had large impacts on birth outcomes; in utero exposure to at least one open-air waste burn increased premature births by 4 percentage points (50%) and low birth weight by 5 to 8 percentage points (80 - 120%). Given previous research documenting the long-run effects of prenatal shocks on adult health, human capital, and labor market outcomes, this suggests open-air waste burning imposes significant costs on populations worldwide.
Keywords: I18; H41; 330; prenatal health; in utero pollution exposure; open-air waste burning